Norepinephrine and its metabolites are involved in the synthesis of neuromelanin derived from the locus coeruleus. (4th September 2015) - Wakamatsu, Kazumasa; Tabuchi, Keisuke; Ojika, Makoto; Zucca, Fabio A.; Zecca, Luigi; Ito, Shosuke
Abstract: In order to elucidate the chemical structure of black to brown pigments, neuromelanins (NMs), in the substantia nigra (SN) and the locus coeruleus (LC) in the central nervous system of humans and other mammalian species during aging, chemical degradative methods are powerful tools. HPLC analysis after hydroiodic acid hydrolysis detected aminohydroxyphenylethylamines, aminohydroxyphenylacetic acids, and aminohydroxyethylbenzenes, which confirmed that SN‐NM and LC‐NM contain melanin derived not only from dopamine and norepinephrine (NE) but also from several other catecholic metabolites, such as 3, 4‐dihydroxyphenylalanine, 3, 4‐dihydroxyphenylacetic acid, 3, 4‐dihydroxymandelic acid, 3, 4‐dihydroxyphenylethanol, and 3, 4‐dihydroxyphenylethylene glycol, in addition to the corresponding Cys‐derivatives in varying degrees. However, hydroiodic acid hydrolysis showed that LC‐NM produced the same degradation products as were detected in SN‐NM. Thus, we needed to develop a new chemical detection method to validate the existence of NE in LC‐NM. In the present study, we report that HCl hydrolysis of LC‐NM in the presence of thioglycolic acid yields new products arising from substitution of the hydroxyl group by thioglycolic acid at the benzyl position of NE and cysteinyl‐NE. This is the first chemical evidence showing that NE and cysteinyl‐NE are incorporated into LC‐NM. Using the chemical degradation methods for the determination of catechols in neuromelanin (NM), we have shown that dopamine (DA), 3, 4‐dihydroxyphenylacetic acid (DOPAC), 3, 4‐dihydroxyphenylethanol (DOPE), and 3, 4‐dihydroxyphenylalanine (DOPA) are mainly responsible for the structure of NM from substantia nigra (SN), while norepinephrine (NE), 3, 4‐dihydroxymandelic acid (DOMA), and 3, 4‐dihydroxyphenylethylene glycol (DOPEG) are additionally responsible for the structure of NM from locus coeruleus (LC). Abstract : Using the chemical degradation methods for the determination of catechols in neuromelanin (NM), we have shown that dopamine (DA), 3, 4‐dihydroxyphenylacetic acid (DOPAC), 3, 4‐dihydroxyphenylethanol (DOPE), and 3, 4‐dihydroxyphenylalanine (DOPA) are mainly responsible for the structure of NM from substantia nigra (SN), while norepinephrine (NE), 3, 4‐dihydroxymandelic acid (DOMA), and 3, 4‐dihydroxyphenylethylene glycol (DOPEG) are additionally responsible for the structure of NM from locus coeruleus (LC).